THE ROLE OF SOCIAL WORKERS TO EMPOWER CHILDREN IN CARE AT THE LKSA NURUL IHSAN ORPHANAGE, BANDUNG - Yolanda, Hana; Sariningsih, Yuce (Journal of Economic Empowerment Strategy (JEES), 2025)
Orphanage​ as institution welfare social own role important in give protection , care and fulfillment need base children who are lost parenting . This institution​ become alternative parenting based institutions that do not only give place live , but also educate and shape character children to be able to independent and empowered competitive in the future . In its implementation, workers social become key main in ensure the parenting process walk in accordance with principlessocial welfare, such as non-discrimination , interests best for children, and children's participation. Social worker own competence professional in understand need child in a way holistic and provides appropriate intervention​ in various situations, including condition psychosocial vulnerable children. They​ No only act as caregiver , but also as facilitator , companion , advocate , and liaison between children , families and institutions related . Therefore that , role social worker become very strategic in ensure quality care and fulfillment rights children in the neighborhood orphanage care . Research This aim For know How role social worker in parenting Children at the LKSA Nurul Ihsan Orphanage in Bandung. Research This use method qualitative with design descriptive . Informant chosen through purposive sampling technique . Data collection technique carried out through observation , interview in-depth , and documentation . Research results show that social worker activities at LKSA Nurul Ihsan run various role . The role carried out at three levels of intervention : micro ( interaction direct with child in matter support emotional and needs basic ), mezzo ( strengthening connection social between group in nursing home ), and macro ( encouraging policies and systems service social policies that favor children ) . In addition , several obstacle in implementation parenting , such as limitations source Power human resources , operational funds and challenges in weave connection between child with family his womb . Although there is various challenges , workers social Keep going make an effort give optimal care through individual, family , and community approaches . Research This give contribution in strengthening role social worker in the environment orphanage care so that they can more effective and sustainable.